2018
DOI: 10.1093/mnras/sty290
|View full text |Cite
|
Sign up to set email alerts
|

Core-powered mass-loss and the radius distribution of small exoplanets

Abstract: Recent observations identify a valley in the radius distribution of small exoplanets, with planets in the range 1.5−2.0 R ⊕ significantly less common than somewhat smaller or larger planets. This valley may suggest a bimodal population of rocky planets that are either engulfed by massive gas envelopes that significantly enlarge their radius, or do not have detectable atmospheres at all. One explanation of such a bimodal distribution is atmospheric erosion by high-energy stellar photons. We investigate an alter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
413
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 446 publications
(431 citation statements)
references
References 34 publications
18
413
0
Order By: Relevance
“…While photoevaporation (e.g. Owen & Wu 2017; Lopez & Rice 2018) is often cited as a potential mechanism for the planet radius valley, other physical mechanisms have been proposed including core-powered mass loss (Ginzburg et al 2018;Gupta & Schlichting 2019a,b), impact erosion via planetesimals (Shuvalov 2009;Schlichting et al 2015;Wyatt et al 2020), and the formation of two distant exoplanet populations due to a gas-poor environment for the rocky planets , which provides an occurrence rate normalized to the width of the bin and therefore is not dependent on choice of grid density. The uncertainties shown are the differences between the median and the 15.87th or 84.13th percentile.…”
Section: Comparison To Fgk Occurrence Ratesmentioning
confidence: 99%
“…While photoevaporation (e.g. Owen & Wu 2017; Lopez & Rice 2018) is often cited as a potential mechanism for the planet radius valley, other physical mechanisms have been proposed including core-powered mass loss (Ginzburg et al 2018;Gupta & Schlichting 2019a,b), impact erosion via planetesimals (Shuvalov 2009;Schlichting et al 2015;Wyatt et al 2020), and the formation of two distant exoplanet populations due to a gas-poor environment for the rocky planets , which provides an occurrence rate normalized to the width of the bin and therefore is not dependent on choice of grid density. The uncertainties shown are the differences between the median and the 15.87th or 84.13th percentile.…”
Section: Comparison To Fgk Occurrence Ratesmentioning
confidence: 99%
“…Recently, Ginzburg et al (2018) and Gupta & Schlichting (2019) showed that the core-powered mass-loss mechanism is also able to reproduce the observed radius valley, even in the absence of photoevaporation. In this mechanism, a planet's internal luminosity drives the loss of its atmosphere (Ginzburg et al 2016(Ginzburg et al , 2018Gupta & Schlichting 2019). The source of this luminosity is a planet's primordial energy from formation, which can be of the order of, or even larger than, its atmosphere's gravitational binding energy.…”
Section: Introductionmentioning
confidence: 98%
“…In this work, we extended previous work on the corepowered mass-loss mechanism (Ginzburg et al 2018;Gupta & Schlichting 2019), and investigated how stellar mass, metallicity and age impact the resulting planet size distribution. We model our host star population on the stars in the CKS survey and investigate, collectively and in isolation, the impact of stellar mass, metallicity and age on the resulting exoplanet size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…There is a degeneracy between the derived core-composition and photoevaporative massloss rates, with lower mass-loss rates favouring lower core densities (Wu 2019;Owen & Adams 2019). Furthermore, alternative hypothesis have been suggested for the origin of the observed gap in the radius distribution, including corepowered mass-loss (Ginzburg et al 2018;Gupta & Schlichting 2019a,b), or two distinct formation pathways for the two sub-groupings. In the latter scenario, the two sub-groupings are water-worlds and rocky, terrestrial planets (Zeng et al 2019).…”
Section: Introductionmentioning
confidence: 99%